Depressed Mood Differentially Mediates the Relationship between Pain Intensity and Pain Disability Depending on Pain Duration: A Moderated Mediation Analysis in Chronic Pain Patients. (29th May 2016) - Probst, Thomas; Neumeier, Susanne; Altmeppen, Jürgen; Angerer, Michael; Loew, Thomas; Pieh, Christoph
Abstract : Research has shown that pain is associated with disability and that depressed mood mediates the relationship between pain and disability. The question of whether duration of pain moderates these effects was addressed in this cross-sectional study with 356 chronic pain patients. A simple mediation model replicated the notion that depressed mood explains a significant proportion of the relationship between pain and disability (in the study at hand: 12%). A moderated mediation model revealed that the indirect effect of pain on disability through depressed mood is moderated by pain duration: while depressed mood did not mediate the effect of pain on disability in chronic pain patients with shorter pain duration, depressed mood significantly mediated the effect pain exerts on disability in chronic pain patients with longer pain duration. Pain duration did not moderate the direct effect of pain on disability. Implications of these findings for the treatment of chronic pain might be that targeting depressed mood is especially relevant in chronic pain patients with longer pain duration to reduce the effect of pain on disability.